Perancangan Aplikasi Mobile GIS Berbasis Android Untuk Informasi Wisata Di Kabupaten Solok - Resma Yanti, Tira; Sularno (CV. ITTC INDONESIA, 2024)
Solok District, a government areas in West Sumatra Province located at the position between 01º 20'27